EDUCATION CHARACTER FIGURES COLLECTION IN READING Hang musk Short Story WORKS Taufik Ikram Jamil - Delmasari, Netriana Delmasari; Rahman, Elmustian Rahman; Jalil, Abdul Jalil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAC: Penelitain is about the characters in Character Education Short Story Reading set Hang musk work Taufik. This study used a qualitative approach and descriptive method that aims to describe the set of characters Characters in Short Story Reading Hang musk work Taufik. Data obtained by reading the short story collection Reading Hang musk works Taufik. Then mark the sentence by having the character in the short story collection Reading Hang musk works Taufik. Based on the results of research, educational characters in the short story collection Reading Hang musk works Taufik has eighteen characters, namely religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, the spirit of nationalism, love of the land water, appreciate the achievements, friends / communicative, love peace, love reading, care for the environment, social care, responsibility. Results of this research is a form to determine the character. Keywords: Character Education People, Short Story Reading Hang musk works Taufik Ikram jamil